2016
DOI: 10.1021/acs.inorgchem.6b01666
|View full text |Cite
|
Sign up to set email alerts
|

Charge and Spin-State Characterization of Cobalt Bis(o-dioxolene) Valence Tautomers Using Co Kβ X-ray Emission and L-Edge X-ray Absorption Spectroscopies

Abstract: The valence tautomeric states of Co(phen)(3,5-DBQ) and Co(tmeda)(3,5-DBQ), where 3,5-DBQ is either the semiquinone (SQ) or catecholate (Cat) form of 3,5-di-tert-butyl-1,2-benzoquinone, have been examined by a series of cobalt-specific X-ray spectroscopies. In this work, we have utilized the sensitivity of 1s3p X-ray emission spectroscopy (Kβ XES) to the oxidation and spin states of 3d transition-metal ions to determine the cobalt-specific electronic structure of valence tautomers. A comparison of their Kβ XES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 100 publications
2
24
0
Order By: Relevance
“… 37 Resonant inelastic X-ray scattering (RIXS) measurements have enabled more detailed analysis of less featured Cu mainlines, leading to distinct assignments of charge-transfer and multielectron transitions achieved at higher resonant excitation energies, corresponding to previously proposed metal–ligand charge transfer (MLCT) features of Cu(I) centers. 38 Classically, nonresonant Kβ mainline spectra have been used for the fingerprinting of transition metal spin states; 39 , 40 however, covalency has been shown to complicate this simple picture. 35 , 41 We note, however, that Cu Kβ mainlines have yet to be thoroughly explored as reporters of oxidation and/or spin state, although the copper mainline is reasoned to follow the same qualitative trends as other d n > 5 transition metals.…”
Section: Introductionmentioning
confidence: 99%
“… 37 Resonant inelastic X-ray scattering (RIXS) measurements have enabled more detailed analysis of less featured Cu mainlines, leading to distinct assignments of charge-transfer and multielectron transitions achieved at higher resonant excitation energies, corresponding to previously proposed metal–ligand charge transfer (MLCT) features of Cu(I) centers. 38 Classically, nonresonant Kβ mainline spectra have been used for the fingerprinting of transition metal spin states; 39 , 40 however, covalency has been shown to complicate this simple picture. 35 , 41 We note, however, that Cu Kβ mainlines have yet to be thoroughly explored as reporters of oxidation and/or spin state, although the copper mainline is reasoned to follow the same qualitative trends as other d n > 5 transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] However,asother factors,including ligand identity, coordination number, and metal spin state,c ontribute to the rising edge position, [10,[12][13][14][15][16][17] caution must be exercised in using the metal K-edge energies as ag eneralized measure of oxidation state.This observation has led to significant debate in the literature as to how edges can be quantitatively interpreted. [18][19][20] Metal L-edge XAS (2p!3d) [21][22][23][24][25][26] can also provide covalencya nd metal oxidation state information, but experimental intensity and covalencyc an only be correlated through computational studies.T hese correlations may be further biased by the computational protocol or individual interpretation. [19,27] In this regard, very similar Cu L-edge data of formal Cu III complexes have been used to both support [27] and dismiss [19] aC u III physical oxidation state assignment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous results showed that the electronic structure of the two valence tautomers are localized, and can be thought of as electron transfer between the ligand and metal, with the metal center changing from LS Co III ↔ HS Co II . [10][11][12][13] One such compound that exhibits valence tautomerism is Co III (Cat-N-SQ)(Cat-N-BQ), where Cat-N-BQ is the singly reduced 2-(2-hydroxy-3,5-di-tert-butylphenyl-imino)-4,6-di-tertbutylcyclohexa-3,5-dienone ligand and Cat-N-SQ is the doubly reduced analogue (Figure 1). This molecule interconverts between LS Co III (Cat-N-SQ)(Cat-N-BQ) and HS Co II (Cat-N-BQ) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Core-level techniques such as L-edge X-ray absorption near-edge structure (XANES) and Kß x-ray fluorescence are sensitive to the spin of the Co center 18,19 and have been successfully used to probe the temperature-dependent spin state of a valence tautomer similar to the one studied here. 11 While ultrafast core-level spectroscopy of Fe complexes has provided important insights into the excited-state electronic structure of molecules such as Fe II polypyridyl complexes, [20][21][22][23][24] femtosecond experiments at the Co edge are less common. [25][26][27][28] The intermediate spin states involved in photoinduced VT have therefore remained elusive.…”
Section: Introductionmentioning
confidence: 99%